How K-Pop Thai Idols Affect Koreans’ Public Perception of Thai People and Multicultural Families: The Case of BLACKPINK’s Lisa - Butsaban, Kamon (Thai Journal of East Asian Studies, 2019)
This study explores what impact Thai K-pop idols have had on the Korean public’s perception of Thai people. The purpose of this study is to analyze the general image of Thai people held by Koreans. To do so, it examined how Koreans’ biased image of Thai people, shaped by the reports of Korean media and looked into one specific incident surrounding BLACKPINK Lisa to analyze the news reports on this incident and the reactions and opinions of Koreans expressed online. Koreans group foreign workers as Southeast Asians and see them as criminals who cause social problems. And Koreans have a biased perception that multicultural families are mostly formed through the marriage between a Korean man and a Southeast Asian woman and think that these families are social minority groups that need to be treated with sympathy. However, the influence of Thai idols on the media such as Lisa on the perceptions of the Korean public is found to be positive. Even when the issue of racial discrimination was raised surrounding Lisa, many netizens criticized and self-reflected on the racial discrimination in Korea.